Ion cyclotron resonance heating for tungsten control in various JET H-mode scenarios. (16th March 2017) - Goniche, M; Dumont, R J; Bobkov, V; Buratti, P; Brezinsek, S; Challis, C; Colas, L; Czarnecka, A; Drewelow, P; Fedorczak, N; Garcia, J; Giroud, C; et al.
Abstract: Ion cyclotron resonance heating (ICRH) in the hydrogen minority scheme provides central ion heating and acts favorably on the core tungsten transport. Full wave modeling shows that, at medium power level (4 MW), after collisional redistribution, the ratio of power transferred to the ions and the electrons vary little with the minority (hydrogen) concentration n H / n e but the high- Z impurity screening provided by the fast ions temperature increases with the concentration. The power radiated by tungsten in the core of the JET discharges has been analyzed on a large database covering the 2013–2014 campaign. In the baseline scenario with moderate plasma current ( I p  = 2.5 MA) ICRH modifies efficiently tungsten transport to avoid its accumulation in the plasma centre and, when the ICRH power is increased, the tungsten radiation peaking evolves as predicted by the neo-classical theory. At higher current (3–4 MA), tungsten accumulation can be only avoided with 5 MW of ICRH power with high gas injection rate. For discharges in the hybrid scenario, the strong initial peaking of the density leads to strong tungsten accumulation. When this initial density peaking is slightly reduced, with an ICRH power in excess of 4 MW, very low tungsten concentration in the core (∼10 −5 ) is maintained for 3 s. MHD activity plays a key role in tungsten transport and modulation of the tungsten radiation during a sawtooth cycle is correlated to the fishbone activity triggered by the fast ion pressure gradient.